PRODUKTIVITAS TENAGA KERJA USAHA TANAMAN MELATI (Jasminum sambac) DI DESA JINGAH HABANG ULU KECAMATAN KARANG INTAN KABUPATEN BANJAR - Fitriadi, Subhan; Triatmoko, Eddy (Chlorophyl, 2022)
The purpose of this research is to know the revenue,the eksplicit cost ,income and , Productivity of labor. This research was conducted in April– Mei 2022 at village Jingah Habang ulu , Banjar regency. The Purposive sampling methode used was by observing 21 farmers in village Jingah Habang Ulu who planted Jasminum sambac plant. The Average result of the revenue is Rp. 3.800.762,/farmer., or Rp. 2.000.401,05 /Ha. the average Total cost is Rp. 2.295.513/farmer, and Average income Rp. 1.505.248/farmer,Total Productivity of labours Rp. 70.710,53 /HKO. the productivity index (IP) shows a value greater than the wage rate of workers / HKO with the prevailing wage rate of Rp. 44,285.7 per HKO and From this result of development of farming Jasminum sambac flant.We believe that it has good prospect and revenue, of the average income ,tecnicall and economically. The contribution of labors in the family can increase farmers’ income and it should be always optimized